The Impact of Natural Resource Abundance on Economic Growth in Nigeria: A Look at History for the Sake of Future - T.A, Mangbon,; S.M., Ojonye, (IJRDO - Journal of Applied Management Science, 2017)
One of the most disturbing characteristics of modern economic growth history is thateconomics that are well-endowed with natural resources have tended to grow slowerthan economies not well endowed with natural resources. While economic historiansand development economists have been puzzled over the addity of resource-poorcountries outperforming the resource-rich ones in their living standards, this studyexamines the impact of natural resource dependency on economic growth in Nigeriawithin the framework of autoregressive methodology. Exploiting a time series data forthe period 1970 – 2014, the study found the speed of adjustment (1 - ) at which percapita income returns to its steady state equilibrium position to be about 39 percentafter it wonders away within two years and that natural resource dependency has notsignificantly enhance economic growth in Nigeria. Based on this finding, it isrecommended that sustainable growth of income per capita can be achieved byinitiating appropriate macroeconomic policies that are aimed at improving the efficiencyand effectiveness of natural resource exploitation in the economy, and a revision offiscal and budgeting systems.